2014
DOI: 10.1371/journal.pone.0091146
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Prevent Imiquimod-Induced Psoriatic Dermatitis through Enhancing Regulatory T Cell Function

Abstract: Psoriasis is a chronic inflammatory skin disease resulting from immune dysregulation. Regulatory T cells (Tregs) are important in the prevention of psoriasis. Traditionally, reactive oxygen species (ROS) are known to be implicated in the progression of inflammatory diseases, including psoriasis, but many recent studies suggested the protective role of ROS in immune-mediated diseases. In particular, severe cases of psoriasis vulgaris have been reported to be successfully treated by hyperbaric oxygen therapy (HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 66 publications
2
74
0
Order By: Relevance
“…Although ROS has been suggested to be pathogenic in Ps and scleroderma (33,34), reduced neutrophil respiratory burst was observed in patients with scleroderma (34), suggesting a protective role for ROS. Recently, imiquimod-induced psoriatic dermatitis was shown to be prevented by ROS (35). Moreover, phagocyteproduced ROS affects rheumatoid arthritis development (36) and β1,3-glucan of Alcaligenes faecalis-induced ROS from monocytes suppressed innate inflammation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although ROS has been suggested to be pathogenic in Ps and scleroderma (33,34), reduced neutrophil respiratory burst was observed in patients with scleroderma (34), suggesting a protective role for ROS. Recently, imiquimod-induced psoriatic dermatitis was shown to be prevented by ROS (35). Moreover, phagocyteproduced ROS affects rheumatoid arthritis development (36) and β1,3-glucan of Alcaligenes faecalis-induced ROS from monocytes suppressed innate inflammation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, macrophage-specific ROS production has been reported to suppress T cell responses and arthritis development [138]. It was previously suggested that Tregs under reduced ROS conditions are hypofunctional [139], and recently, Treg hyperfunctionality in elevated levels of ROS in an IMQ-induced Ps dermatitis model was observed [140]. Treg hyperfunctionality with high levels of ROS is suggested to operate as a compensatory mechanism to overcome the damaging effects of ROS and thereby decrease Ps disease activity [140].…”
Section: Protective Nature Of Rosmentioning
confidence: 99%
“…It was previously suggested that Tregs under reduced ROS conditions are hypofunctional [139], and recently, Treg hyperfunctionality in elevated levels of ROS in an IMQ-induced Ps dermatitis model was observed [140]. Treg hyperfunctionality with high levels of ROS is suggested to operate as a compensatory mechanism to overcome the damaging effects of ROS and thereby decrease Ps disease activity [140]. Thus, the restoration of impaired Treg functions could be a possible therapeutic strategy for Ps patients.…”
Section: Protective Nature Of Rosmentioning
confidence: 99%
“…Recent reports have proposed opposing views. Kim et al [41] investigated IMQ-induced psoriatic dermatitis in association with Treg function both in elevated and lowered levels of ROS and found that IQM-induced psoriasis was attenuated at elevated levels of ROS and was aggravated at reduced levels of ROS. Furuhashi et al [42] found that photo (chemo) therapy reduced circulating Th17 cells and restored circulating regulatory T cells in psoriasis.…”
Section: Discussionmentioning
confidence: 99%